Domestikasi Hewan Liar Zona Sub-optimal Rawa Lebak Indralaya, Sumatera Selatan: Kasus Berang-berang (Lutra sumatrana) - Hanifa Marisa (Seminar Nasional Lahan Suboptimal, 2018)
Marisa et al, 2019. Domestication a Wild Animal Species of  Sub-optimal Zone, in Indralaya Swampy Area, South Sumatra; The Case of Hairy Nosed Otter (Lutra sumatrana). pp. 376-383. An observation had been done to publish a success domestication  of a wild animal in Indralaya swampy area, (sub-optimal agricultural zone) , South Sumatra at last September 2018. A pair of hairy nosed otter (Lutra sumatrana) had een care during three years, with 3.2 – 4 kg weight,  50 – 60 cm bofy  length,  and consumed 1 kg food (hens/cock heads), never overcome sick, and looks like commonly pet.  These otters would come back to their home, even be released to the nature.